A principal components/singular spectrum analysis approach to ENSO and PDO influences on rainfall in western Irán (2014)
ABSTRACT : This paper analyzes the spatio-temporal variability of precipitation in western Iran by means of the Standardized Precipitation Index (SPI), calculated in annual and seasonal aggregations for wet and dry conditions over 46 synoptic stations with monthly data from 1957 to 2008. Regions of homogeneous SPI realizations were delimited using principal components analysis (PCA) to highlight major variation modes distinguishable in the basin and singular spectrum analysis (SSA) was performed over the reconstructed values of SPI to identify their oscillation modes. Extreme SPI values associated with El Niño–Southern Oscillation (ENSO) and Pacific Decadal Oscillation (PDO) were also evaluated. Results show two significant oscillations around 4 and 8 years on the SPI with an increase in precipitation variability since 1990 and a tendency to have less rain during the cold season and more rain during the warm season. We calculated standardized products among SPI, ENSO, and PDO to determine years in which the indices reinforce each other, 1986, 1992, 1999, and 2008 being particularly significant in the associations. These results are important for water managers in western Iran because they indicate significant changes in precipitation regimes associated with ENSO and PDO signals that will help to assess the occurrence of droughts and floods in the area